Social capital and public health: responding to the COVID-19 pandemic - Anna S. Y. Wong; Jillian C. Kohler (BMC, 2020)
Abstract Background As countries continue to respond to the COVID-19 pandemic, the importance of ensuring that fair and equal access to healthcare for all is more urgent than ever. Policies that promote social capital building along all levels of society may offer an important avenue for improved healthcare delivery and health systems strengthening in the COVID-19 response. Main body In reference to the established and emerging literature on social capital and health, we explore the role of social capital in the COVID-19 health policy response. We analyse current research with respect to mental health, public health policy compliance, and the provision of care for vulnerable populations, and highlight how considerations of bonding, bridging, and linking capital can contribute to health systems strengthening in the context of the COVID-19 response and recovery effort. Conclusions This article argues that considerations of social capital - including virtual community building, fostering solidarity between high-risk and low-risk groups, and trust building between decision-makers, healthcare workers, and the public - offer a powerful frame of reference for understanding how response and recovery programs can be best implemented to effectively ensure the inclusive provision of COVID-19 health services.